A utilização democrática e pedagógica de páginas criadas em ambientes virtuais para a comunicação entre equipe gestora e a comunidade de escolas estaduais - Paulesini, Joana Vera Simacek (2008)
The ICT for Principal Project ordered by the Secretary of Education of São Paulo State and conceived by the Pontifical Catholic University of São Paulo in partnership with Microsoft, viewed to develop the training of manegers in the use of Information and Communication Technologies applied in the school management and in the school´s day to day activity. In this context the work was focused on the analysis of the kind of communication established between the managing teams of six public schools of São Paulo and their communities throug the sites created by the managers during their participation on the project and made avaible on the Internet. During these two years process, information was obteined by analysing the sites, questionaries answered by the managers and by establishing focal groups. The data were analyzed in the light of theoretical references related to questions like participation, the use of thecnologies inside the school and the legislation of the Secretary of Education of São Paulo State, that rules the issues referred to herein. The participation of the school´s managing team on the ICT for Principal Project enabled the creation of the sites inserted on the Internet. The implementation of these sites occurred because the managing team remained at the school and changed their posture by assuming the coordination of the process together with the other members of the school community. On the other hand, the high rotativity of the managing team members and back of availability of technological resources like computers with Internet access at schools were factors that made the site implementation in the community rather difficut. Following the phase of site implementation, the managing teams obtained the participation of the community only in pedagogical matters and events; the participation at Parents and Teachers Association and the Schoool Council did not increase. The community did not consider the site avaiable on the Internet as a space where they could post their doubts regarding their daily life, thus surpassing the issues related to the school, Consequently, the managing team did not proceed with the discussion of the problems referred to the matter and took distance to the community